2005
DOI: 10.1080/17451000500459795
|View full text |Cite
|
Sign up to set email alerts
|

Does temperature preference relate to the anaerobic capacity of Atlantic cod (Gadus morhuaL.) with different haemoglobin phenotype?

Abstract: 2005) Does temperature preference relate to the anaerobic capacity of Atlantic cod (Gadus morhua L.) with different haemoglobin phenotype?, Marine Biology Research, 1:6, 411-416, AbstractThe effect of Hb-I* phenotype on white muscle lactate dehydrogenease (LDH, E. C. 1.1.1.27) activity and buffering capacity was studied in Atlantic cod (Gadus morhua ), acclimated and measured at temperatures near their behavioral temperature preference. It was hypothesized that these conditions would optimize biochemical proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Further, Colosimo et al (2003) concluded that physiological adaptation of the individual, not Hb genotype, was the main factor shaping the growth and Hb binding characteristics of Atlantic cod at various temperatures. Thus, when these results are combined with a lack of physiological differences among cod HbI genotypes (Jordan et al 2005; this study) and the inability of Herbert et al (2006) to relate differences in Hb functional properties with the swimming capacity and hypoxia tolerance of marine fishes (including cod), the prevailing evidence (1) suggests that the adaptive functional significance of HbI genotypes has been overestimated and (2) raises the possibility that while HbI polymorphism does not directly influence cod in vivo blood oxygen transport or thermal biology, Hb isoforms may have evolved in parallel or be linked with other traits that have important implications for blood oxygen transport/utilization at different temperatures.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, Colosimo et al (2003) concluded that physiological adaptation of the individual, not Hb genotype, was the main factor shaping the growth and Hb binding characteristics of Atlantic cod at various temperatures. Thus, when these results are combined with a lack of physiological differences among cod HbI genotypes (Jordan et al 2005; this study) and the inability of Herbert et al (2006) to relate differences in Hb functional properties with the swimming capacity and hypoxia tolerance of marine fishes (including cod), the prevailing evidence (1) suggests that the adaptive functional significance of HbI genotypes has been overestimated and (2) raises the possibility that while HbI polymorphism does not directly influence cod in vivo blood oxygen transport or thermal biology, Hb isoforms may have evolved in parallel or be linked with other traits that have important implications for blood oxygen transport/utilization at different temperatures.…”
Section: Discussionmentioning
confidence: 95%
“…1 in Brix et al 2004), growth rate (Naevdal et al 1992;Brix et al 2004;Imsland et al 2004Imsland et al , 2005Imsland et al , 2007Jordan et al 2006), and in vitro Hb functional properties (erythrocyte suspensions: Karpov and Novikov 1981;stripped Hb: Brix et al 1998 among Atlantic cod Hb genotypes, several authors have suggested that Hb polymorphism in this species is associated with differences in physiological performance. However, with the exception of a recent article showing that white muscle lactate dehydrogenase activity and buffering capacity are similar (Jordan et al 2005), there have been no direct investigations of physiological differences among cod Hb genotypes. In this study, we generated a single family comprised of the three main Hb genotypes (HbI-1/1, HbI-1/2, and HbI-2/2) and evaluated their metabolic and cortisol responses to an acute thermal challenge and their hypoxia tolerance.…”
Section: Discussionmentioning
confidence: 99%